Trend Judi Online Pada Kelompok Remaja: Faktor Resiko dan Dampak Sosial - Machfud, Mochammad; Khodijah, Khodijah (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2024)
The development of technology has changed the way gambling is done, from being done in physical locations such as casinos to being more accessible through digital platforms connected to the internet. Now, one can easily access gambling games online by simply using a digital device and an internet connection. While this ease of access provides greater convenience and privacy, it is important to remember that gambling remains a prohibited or restricted activity in many countries. As such, there are concerns regarding the increasing involvement of individuals, especially adolescents, in online gambling which could potentially have a negative impact on aspects of their lives. This study has a comprehensive objective in describing and analyzing adolescents' participation in online gambling. This includes evaluating the risks faced by adolescents as well as the social impacts that occur due to their involvement in online gambling practices. The research method used by the researcher is a descriptive method with a library research approach as the foundation of this research. This approach involves collecting data from various sources such as books, journal articles and relevant internet sources, in order to analyze the factors that influence the popularity of online gambling among teenagers and highlight its risks and negative impacts in society. This research is expected to identify the factors driving teenagers' interest in online gambling, detail the risks associated with teenagers' involvement in this activity, and reveal the various negative social impacts arising from the practice of online gambling among teenagers in society.